2014
DOI: 10.1063/1.4875495
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared photoactive Cu3BiS3 thin films by co-evaporation

Abstract: Investigation of combinatorial coevaporated thin film Cu2ZnSnS4. I. Temperature effect, crystalline phases, morphology, and photoluminescence Semiconducting Cu 3 BiS 3 (CBS) thin films were deposited by co-evaporation of Cu, Bi elemental metallic precursors, with in situ sulphurisation, using a quartz effusion cell. Cu 3 BiS 3 thin films were structurally characterized by XRD and FE-SEM. The chemical bonding of the ions was examined by XPS. As deposited films were demonstrated for metal-semiconductor-metal nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…However, the progress of chemical methods suitable for the synthesis of a ternary Cu 3 BiS 3 still remains a major challenge. The wide range of techniques that have been employed to prepare Cu 3 BiS 3 semiconductor material had been reviewed with the hope of distinguishing new [43,57]; nanosheets (c) [42]; nanorods (d, e) [37,47]; dendrites (f) [56]; flower-like hierarchical (g) [38]; corallike (h) [60]; bent-like nanorods (i) [39]; spherical nanoparticles (j) [55]; nanoneedle-like (k) [29] and 3D flower-like ball (l) [45] morphologies of Cu 3 BiS 3 paths for productive research based on the present author's work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the progress of chemical methods suitable for the synthesis of a ternary Cu 3 BiS 3 still remains a major challenge. The wide range of techniques that have been employed to prepare Cu 3 BiS 3 semiconductor material had been reviewed with the hope of distinguishing new [43,57]; nanosheets (c) [42]; nanorods (d, e) [37,47]; dendrites (f) [56]; flower-like hierarchical (g) [38]; corallike (h) [60]; bent-like nanorods (i) [39]; spherical nanoparticles (j) [55]; nanoneedle-like (k) [29] and 3D flower-like ball (l) [45] morphologies of Cu 3 BiS 3 paths for productive research based on the present author's work.…”
Section: Discussionmentioning
confidence: 99%
“…In Cu 3 BiS 3 semiconductor, these three trapping levels may be associated with the presence of structural defects and unintentional impurities. Thereafter, Murali et al [29] in 2014 reported the deposition of Cu 3 BiS 3 thin films by co-evaporation of the Cu, Bi elemental precursors on a Mo-glass substrate with in situ sulfurization using a quartz effusion cell. irrespective of the Cu/Bi mass ratio.…”
Section: Vacuum-based Evaporation Deposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24,33,34 ] Several methods have been reported for the synthesis of Cu 3 BiS 3 nanomaterials, including solvothermal route, [ 35,36 ] cyclic microwave radiation, [ 37 ] and coevaporation. [ 38,39 ] There are few papers reporting the synthesis of Cu 3 BiS 3 nanostructures using thermal decomposition of precursor complexes. Here, hydrophobic Cu 3 BiS 3 NPs were synthesized by the thermal decomposition of Cu(S 2 CNEt 2 ) 2 and Bi(S 2 CNEt 2 ) 3 precursors in oily mixed solvent and then the produced Cu 3 BiS 3 NPs were coated with amphiphilic polyvinylpyrrolidone (PVP) through the ligand exchange.…”
Section: Hydrophilic Cu 3 Bis 3 Nanoparticles (Nps) Have Been Preparementioning
confidence: 99%
“…Ternary semiconductor nanomaterials are able to inherit the properties from their parent binary materials . Copper bismuth sulfide (CBS) (such as Cu 3 BiS 3 , Cu 4 BiS 4 , and CuBiS 2 ) nanostructures are usually p‐type semiconductors; thus, these nanomaterials may have many copper vacancies and exhibit the NIR absorption as with self‐doped copper chalcogenides, and CBS nanostructures have the potential to be used as CT contrast agents, similar to Bi 2 S 3 nanostructures, which have been widely studied as CT contrast agents due to the large X‐ray attenuation coefficient of bismuth . Consequently, CBS nanostructures can theoretically show both the NIR response and imaging response.…”
mentioning
confidence: 99%